The Role of Public Accountants in Fraud Prevention and Detection in the Taxation Sector during Covid-19 - Widiyati, Dian; Valdiansyah, Riyan Harbi; Meidijati, M; Hendra, H (Manunggal Halim Jaya, 2021)
Until now, there have been many cases of tax evasion that have occurred in Indonesia. Fraud is an act of deviation or omission that is intentionally carried out to deceive, or other parties suffering losses or fraud perpetrators obtaining financial benefits, either directly or indirectly. The design of this research based on literature review. Tax policy in the majority of countries was oriented towards mitigating health impacts and preventing economic pressure. Recently we have also seen other motives that various countries in the world want to achieve as Secretary-General Tax Report to G-20 Finance Ministers and Central Bank Governors. Quick responses through various tax relaxations came through twenty-two legal products. One of the things that is being studied is changes to VAT policy scheme. Currently, the Indonesian Institute of Certified Public Accountants is submitting an exposure draft related to the SJI. Tax incentives provided during the COVID-19 pandemic has the potential to be misused. The role of Public Accountants in preventing and detecting fraud in the taxation sector can be maximized if the public accountant carries out adequate procedures in accordance with applicable auditing standards. Public accountants need to increase the independence of each individual e.g., Continuing Education Program (PPL).